Identification and inheritance of an Rdc gene resistance to soybean stem canker (Diaporthe phaseolorum var. caulivora) - Peruzzo, Alejandra María (2019)
Soybean stem canker (SSC) is caused by two varieties of the fungus Diaporthe phaseolorum: var. meridionalis (Dpm) and var. caulivora (Dpc). The objective was to identify and characterize the mode of inheritance of Rdc genes through a classical Mendelian analysis. Resistant (R) and susceptible (S) genotypes were used to make 288 RxS and 132 RxR crosses, including their reciprocals. Segregating F2 generations were obtained by self-fertilization of the respective F1. The incorporation of codominant molecular markers (Single Nucleotide Polymorphism, SNP) allowed the molecular validation of 48.75% of F1 heterozygous individuals. Parents (R and S), F1 individuals, and F2:3 families (Progeny Test, PT) from COD 1–258-2 population were inoculated with an isolate of Dpc (Dpc16), previously identified morphologically and molecularly. The assay showed 21 F2:3 families categorized as R, 42 segregated R and S, and 11 as S. Particularly, this F3 population showed 466 individuals R and 274 S. The chi-square goodness of fit test verified that phenotypic segregation for individual plants in F3 adjusted to a 5:3 ratio (R:S) and the PT results corresponded to the genotypic ratios (1RR: 2Rr: 1rr) of F2 individuals. Results allowed the identification of a major resistance gene of simple Mendelian inheritance to SSC that was named Rdc1. Also, independent segregation 9:3:3:1 was verified between this Rdc1 gene and the gene that regulates flower colour, a typical phenotypic marker in soybean. Based on literature review, this is the first report on resistance genes (Rdc) identified for SSC caused by Dpc.